Strategic fit - the missing link between strategy formulation and strategy execution - Muhamad Yusoff, Muhamad Roslan (2015)
A wide framework for strategy formulation and procedures for its implementation are designed and used in last few decades by a large number of firms, with strong conviction that the expected outcome will be as precise as it is claimed. A study of 750 of the biggest U.S. business catastrophes from the past 25 years pointed at popular but risky strategies, which were used by their firm. Strategists find it difficult to cope with the complexity and trim it to a manageable extent. The complex interactions of variables from the perspective of geopolitics, technical innovation, capital market swings due to national economic policies, direct and indirect competition, varying consumer preferences etc insists the organization to change the way strategies are visualized and alter the methods of implementation. The organizational behavior determinants from internal and external contingencies decide the course of strategy implementation and complexities arising in it. The implementation may not take place as expected from formulation due to concealed gaps and may result in a deficient performance. This paper is an effort to identify the determinants of a commendable strategic fit to create a win-win situation; by encompassing the factors creating the gap and evaluating the performance perimeters consequent to dimensions of a strategic fit.